1979
DOI: 10.1113/jphysiol.1979.sp012758
|View full text |Cite
|
Sign up to set email alerts
|

Non‐parallel enzyme secretion from rat pancreas in vitro studies.

Abstract: SUMMARY1. The relative variations of rat pancreatic amylase versus lipase and chymotrypsinogen secretions have been studied in vitro with the help of two different techniques: in situ organ perfusion and incubation of pancreatic lobules.2. In experiments on the perfused pancreas, with 8 C u. kg-1 hr-1 secretin added to the perfusion fluid, cholecystokinin-pancreozymin (8 ID u. kg-1) or pilocarpine (15 mg kg-1) both resulted in a significant change in the enzyme proportions in the juice.3. In experiments on pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Our experiments also suggest that junctional coupling contributes to the contact-dependent mechanism which enhances the recruitment of secreting cells and their individual output. These observations strengthen the view that direct interactions between acinar cells are essential in the control of pancreatic secretion.o 1994 Wdey-Liss, Inc.The observation within intact pancreas of acini showing morphological and biochemical differences (Bendayan, 1985; Hellman et al, 1962;Kramer and Tan, 1968) and the findings that different stimuli elicit the secretion of variable mixtures of pancreatic enzymes (Adelson and Miller, 1985;Beaudoin et al, 1983;Dagorn and Estival, 1979;Majumdar et al, 1985;Rothman, 1976) indicate that the secretion of the exocrine pancreas may not be similarly contributed by each subunit of the gland.To assess whether this variable secretory contribution results from a different intrapancreatic environment or from specific, intrinsic characteristics of individual acini, we previously developed an immunological assay which permits us to simultaneously compare the amylase secretion of single acini under rigorously identical conditions (Bosco et al, 1988). Using this assay, we have shown that individual acini dis-0 1994 WILEY-LISS, INC persed from normal rat pancreas release amylase at rather different rates, probably due to intrinsic differences in their secretory machinery (Bosco et al, 1988).…”
mentioning
confidence: 53%
“…Our experiments also suggest that junctional coupling contributes to the contact-dependent mechanism which enhances the recruitment of secreting cells and their individual output. These observations strengthen the view that direct interactions between acinar cells are essential in the control of pancreatic secretion.o 1994 Wdey-Liss, Inc.The observation within intact pancreas of acini showing morphological and biochemical differences (Bendayan, 1985; Hellman et al, 1962;Kramer and Tan, 1968) and the findings that different stimuli elicit the secretion of variable mixtures of pancreatic enzymes (Adelson and Miller, 1985;Beaudoin et al, 1983;Dagorn and Estival, 1979;Majumdar et al, 1985;Rothman, 1976) indicate that the secretion of the exocrine pancreas may not be similarly contributed by each subunit of the gland.To assess whether this variable secretory contribution results from a different intrapancreatic environment or from specific, intrinsic characteristics of individual acini, we previously developed an immunological assay which permits us to simultaneously compare the amylase secretion of single acini under rigorously identical conditions (Bosco et al, 1988). Using this assay, we have shown that individual acini dis-0 1994 WILEY-LISS, INC persed from normal rat pancreas release amylase at rather different rates, probably due to intrinsic differences in their secretory machinery (Bosco et al, 1988).…”
mentioning
confidence: 53%
“…We intended to reinvestigate that question by comparing in the anaesthesized rat the rates of appearance of newly synthe sized proteins in pancreatic juice. This model seems sometimes better adapted than in vitro systems for comparing the secretion rate of individual enzyme species since it allows demonstration of short-term changes in en zyme proportions in juice upon stimulation [5] although no such change could be evi denced in the lobule system used by Tartakoff et al [6,19]. Our results show that trypsinogen and chymotrypsinogen are trans ported through the acinar cell at a much fas ter rate than amylase, lipase being in an inter mediate situation.…”
mentioning
confidence: 68%
“…Chymotrypsin was assayed according to Hummel [8], after activation by bovine trypsin [6], Amylase was assayed according to A'oelting and Bernfeld [ 16]. Total protein concentration was measured by UV spectrophotometry (E]< *1 = 20 at 280 nm).…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Studies by several groups of workers on the exocrine pancreas, P. KANAGASUNTHERAM AND SOH CHAN LIM both in vivo and in vitro, have however, failed to establish unequivocally the parallelism or otherwise of pancreatic enzyme secretion (for review see Case, 1978). While some workers (Tartakoff, Jamieson, Scheele & Palade, 1975;Scheele & Palade, 1976;Steer & Glazer, 1976) have reported parallel release of several of the pancreatic enzymes under both basal as well as stimulated conditions, others, in particular Rothman and co-workers, have observed preferential discharge of certain enzymes (Rothman & Isenman, 1974;Adelson & Rothman, 1975;Dagorn & Estival, 1979). In an attempt to account for non-parallel secretion of digestive enzymes by the exocrine pancreas, Rothman has proposed an alternative model for secretion (Rothman & Isenman, 1974;Rothman, 1975) (Scheele & Palade, 1975 (Wallach & Schramm, 1971) which is also secreted together with the enzymes.…”
Section: Introductionmentioning
confidence: 99%